2018
DOI: 10.1158/1078-0432.ccr-17-3347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prexasertib, a Checkpoint Kinase 1 Inhibitor, in a Phase Ib Study of Patients with Squamous Cell Carcinoma

Abstract: Prexasertib, a checkpoint kinase 1 inhibitor, demonstrated single-agent activity in patients with advanced squamous cell carcinoma (SCC) in the dose-escalation portion of a phase I study (NCT01115790). Monotherapy prexasertib was further evaluated in patients with advanced SCC. Patients were given prexasertib 105 mg/m as a 1-hour infusion on day 1 of a 14-day cycle. Expansion cohorts were defined by tumor and treatment line. Safety, tolerability, efficacy, and exploratory biomarkers were analyzed. Prexasertib … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 42 publications
(58 reference statements)
7
69
0
Order By: Relevance
“…Hauge et al [32] reported that excessive p21 limits S phase DNA damage caused by the WEE1 inhibitor MK1775 (adavosertib), again supporting the notion that negative regulators of CDK2 may limit cytotoxicity to agents that target the ATR-CHK1-WEE1 pathway. Although these observations have supported cyclin E-centered hypothesis for prexasertib response, clinical actionability of this marker is limited by insufficient predictive power [12,13]. In addition, our preclinical data further supports this limitation in applicability as a single marker for patient selection.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Hauge et al [32] reported that excessive p21 limits S phase DNA damage caused by the WEE1 inhibitor MK1775 (adavosertib), again supporting the notion that negative regulators of CDK2 may limit cytotoxicity to agents that target the ATR-CHK1-WEE1 pathway. Although these observations have supported cyclin E-centered hypothesis for prexasertib response, clinical actionability of this marker is limited by insufficient predictive power [12,13]. In addition, our preclinical data further supports this limitation in applicability as a single marker for patient selection.…”
Section: Discussionsupporting
confidence: 62%
“…Prexasertib is a small molecule kinase inhibitor displaying high selectivity for CHK1 followed by CHK2 [5]. An initial search for predictive biomarkers in these patients revealed a signal centered on cyclin E1, such as LOF mutations in the E3 ubiquitin ligase FBXW7 [12] and elevation of cyclin E1 protein levels [13]. Here, we confirmed that FBXW7 knockdown is associated with elevation of cyclin E1 protein levels, CDK2 activation, CHK1 signaling, and increased RS (as measured by pRPA2) and DNA damage (evidenced by γH2AX).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Checkpoint inhibitors are a powerful new class on immunotherapies that are actively being investigated in several other types of cancers 19,20 . Anti-PD-1 antibodies have demonstrated durable response and prolonged overall survival in a broad variety of cancer types 4,21 including advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%